A connecticut yankee in King Arthur's court - Twain, Mark, 1835-1910; New Editions ([Hellinikon, Greece] : New Editions, 2000)
The story explains the tale of Hank Morgan, a 19th-century resident of Hartford, Connecticut who awakens to find himself inexplicably transported back in time to early medieval Britain at the time of the legendary King Arthur
Title from container
Keywords: Americans -- Great Britain -- Fiction; Knights and knighthood -- Fiction; Kings and rulers -- Fiction; Time travel -- Fiction